Improving Adherence to Antiretroviral Therapy for Youth Living with HIV/AIDS: A Pilot Study Using Personalized, Interactive, Daily Text Message Reminders - Dowshen, Nadia; Kuhns, Lisa M; Johnson, Amy; Holoyda, Brian James; Garofalo, Robert (JMIR Publications, 2012)
BackgroundFor youth living with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS), nonadherence to antiretroviral therapy (ART) can lead to poor health outcomes and significantly decreased life expectancy. ObjectiveTo evaluate the feasability, acceptability, and preliminary efficacy of short message service (SMS) or text message reminders to improve adherence to ART for youth living with HIV/AIDS. MethodsWe conducted this prospective pilot study using a pre-post design from 2009 to 2010 at a community-based health center providing clinical services to youth living with HIV/AIDS. Eligibility criteria included HIV-positive serostatus, age 14-29 years, use of a personal cell phone, English-speaking, and being on ART with documented poor adherence. During the 24-week study period, participants received personalized daily SMS reminders and a follow-up message 1 hour later assessing whether they took the medication, and asking participants to respond via text message with the number 1 if they took the medication and 2 if they did not. Outcome measures were feasibility, acceptability, and adherence. Self-reported adherence was determined using the visual analog scale (VAS) and AIDS Clinical Trial Group (ACTG) questionnaire 4-day recall. Viral load and CD4 cell count were followed as biomarkers of adherence and disease progression at 0, 12, and 24 weeks. ResultsParticipants (N = 25) were mean age 23 (range 14-29) years, 92% (n = 23) male, 60% (n = 15) black, and 84% (n = 21) infected through unprotected sex. Mean VAS scores significantly increased at 12 and 24 weeks in comparison with baseline (week 0: 74.7, week 12: 93.3, P < .001; week 24: 93.1, P < .001). ACTG questionnaire 4-day recall also improved (week 0: 2.33, week 12: 3.24, P = .002; week 24: 3.19, P = .005). There was no significant difference in CD4 cell count or viral load between baseline and 12- or 24-week follow-up, although there was a trend toward improvement of these biomarkers and a small to moderate standardized effect size (range of Cohen d: -0.51 to 0.22). Of 25 participants, 21 (84%) were retained, and 20 of the 21 (95%) participants who completed the study found the intervention helpful to avoid missing doses. ConclusionsIn this pilot study, personalized, interactive, daily SMS reminders were feasible and acceptable, and they significantly improved self-reported adherence. Larger controlled studies are needed to determine the impact of this intervention on ART adherence and other related health outcomes for youth living with HIV/AIDS.